Characterization of Delamination Effect on Free Vibration of Composite Laminates Plate Using High Order Shear Deformation Theory - Hadi, Nabil Hassan; Ameen, Kayser Aziz (Al-Khwarizmi Engineering Journal, 2011)
A dynamic analysis method has been developed to investigate and characterize embedded delamination on the dynamic response of composite laminated structures. A nonlinear finite element model for geometrically large amplitude free vibration intact plate and delamination plate analysis is presented using higher order shear deformation theory where the nonlinearity was introduced  in the Green-Lagrange sense. The governing equation of the vibrated plate were derived using the Variational approach. The effect of different orthotropicity ratio, boundary condition and delamination size on the non-dimenational fundamental frequency and frequency ratios of plate for different stacking sequences are studied. Finally the discrepancy of the results was 17.4906% when the severe nonlinearity is considered.